Моделювання параметрів джерел розподільної генерації в інтегрованих електро-постачальних системах із урахуванням невизначеності інформації - Ярмолюк, О.С. (Технічна електродинаміка, 2012)
Efficient operation of electrical networks is impossible without high-quality and reliable information. This requirement even will grow in the process of further formation of integrated distribution systems. It is evident that the development of information support will be compensated by the additional uncertainty introduced due to the active use of alternative energy sources. This paper proposed an approach that allows one the way to optimal formation of fuzzy estimates of alternative energy sources. To realize this problem the mathematical approach of the fuzzy sets theory is used.